أحكام النقاد القدامى على شعر المديح (الرغبة أنموذجاً) (Albayan Scientific Journal, 2023)
This study deals with the critical judgments made by critics on praise poetry, in order to identify them and to reveal the great role of praise motives in guiding these critical judgments. Its importance appears in that it tries to attribute praise to its motives and to carefully read the rulings decided by the critics according to these motives to indicate whether they are correct or in need of evaluation. The study relied on the descriptive and analytical method, and reached a set of results, the most important of which is that, the judgment on praise poetry was greatly influenced by the motive of desire, which is a motive that distracts critics from looking at praise as an art that has expressive and aesthetic and influential characteristics, and has its moral social and educational mission. Its subjective and human characteristics. They went beyond art and looked at the relationship between praising poet and praise, and in light of this view were their judgments.